Biomimicking fiber platform with tunable stiffness to study mechanotransduction reveals stiffness enhances oligodendrocyte differentiation but impedes myelination through YAP-dependent regulation - Ong, William (2020)
A key hallmark of many diseases, especially those in the central nervous system (CNS), is the change in tissue stiffness due to inflammation and scarring. However, how such changes in microenvironment affect the regenerative process remains poorly understood. Here, we report a biomimicking fiber platform that provides independent variation of fiber structural and intrinsic stiffness. To demonstrate the functionality of these constructs as a mechanotransduction study platform, we utilized these substrates as artificial axons and independently analysed the effects of axon structural vs. intrinsic stiffness on CNS myelination. While studies have shown that substrate stiffness affects oligodendrocyte differentiation, the effects of mechanical stiffness on the final functional state of oligodendrocyte (i.e. myelination) has not been shown prior to this. Here, we demonstrate that a stiff mechanical microenvironment impedes oligodendrocyte myelination, independently and distinctively from oligodendrocyte differentiation. We identified YAP to be involved in influencing oligodendrocyte myelination through mechanotransduction. The opposing effects on oligodendrocyte differentiation and myelination provide important implications for current work screening for promyelinating drugs, since these efforts have focused mainly on promoting oligodendrocyte differentiation. Thus, our novel platform may have considerable utility as part of a drug discovery programme in identifying molecules that promote both differentiation and myelination.